Validation of the Spanish version of the oral health impact profile to assess an association between quality of life and oral health of elderly Chileans. (11th March 2014) - León, Soraya; Bravo‐Cavicchioli, Daniel; Giacaman, Rodrigo A.; Correa‐Beltrán, Gloria; Albala, Cecilia
Abstract : Objective: To validate the Spanish version of the OHIP‐49 among elderly population. Background: Oral health, as a predictor of quality of life, can be evaluated using validated instruments. One of the most commonly used instruments worldwide is the Oral Health Impact Profile‐49 (OHIP‐49). This instrument has not yet been validated in Chilean older adults. Materials and methods: Interviews and clinical exams were performed in a convenience sample of eighty‐five elderly participants aged 60 or more years (mean 69.02 ± 7.82 years). Socio‐demographic and clinical variables were analysed: number of teeth, caries, periodontal and prosthetic treatment needs and prosthetic functionality. Results: High internal consistency values were obtained for both the OHIP‐49 Sp instrument (0.990) and all of its dimensions (0.875–0.995). The average score of the OHIP‐49 Sp was 62.54 ± 43.73. Significantly higher OHIP‐49 Sp scores were observed in participants with caries ( p  = 0.01), in those needing complex periodontal treatment ( p  = 0.0001) and those in need of dental prostheses ( p  ≤ 0.0001). Conclusion: The OHIP‐49 Sp proved to be a valid tool to assess oral health‐related quality of life, when tested in Chilean older adults.